Serological investigation and isolation of Salmonella abortus equi in horses in Xinjiang - Zhanhai Mai; Han Fu; Ronghao Miao; Chong Lu; Xiaosong Zhang; Ziwen Yuan; Peng Ji; Yongli Hua; Chen Wang; Yuhui Ma; Haifeng Deng; Yanming Wei (BMC Veterinary Research, 2024)
Abstract Background Salmonella enterica subspecies enterica serovar abortus equi (S. abortus equi) is one of the main pathogens that causes abortion in pregnant horses and donkeys, which was highly infectious and greatly restricts the healthy development of the horse industry. Objectives In order to investigate the prevalence and biological characteristics of S. abortus equi in different regions and breeds of horses in Xinjiang. Methods This study conducted ELISA detection of S. abortus equi antibodies on serum samples of 971 horses collected from three large-scale horse farms and five free-range horse farms in Yili Prefecture and Bayingol Mongolian Autonomous Prefecture of Xinjiang from 2020 to 2023. On this basis, bacterial isolation, culture, identification, and drug sensitivity tests were conducted on 42 samples of aborted foal tissues and 23 mare vaginal swabs. Results The results showed that the positive rate of S. abortus equi antibody was as high as 20.91% in 971 horse serum samples. Among them, the positive rate in the Ili region (29.09%) was significantly higher than that in the Bayingole region (11.24%), and the positive rate in mares (22.45%) was higher than that in stallions (14.05%). In terms of horse breeds, the positive rates of self-propagating thoroughbred horses, half-bred horses, Ili horses and Yanqi horses were 43.22%, 28.81%, 14.72% and 11.24% respectively. In addition, S. abortus equi was more susceptible to juvenile and elderly horses, with positive rates of 70.00%and 41.86%, respectively, both of which were significantly higher than young (10.97%) and adult (19.79%) horses. Further, 9 strains of S. abortus equi were obtained through bacterial isolation, culture and identification, which were resistant to five antibiotics (Clarithromycin, Clindamycin, penicillin, Sulfamethoxazole and Rifampicin), and sensitive to 13 antimicrobial agents (Amoxicillin, Ciprofloxacin and Gentamicin, et al.). Conclusion There was a high infection rate of S. abortus equi in Ili Prefecture and self-propagating thoroughbred horses, and juvenile or old mares were more susceptible, which will provide scientific basis for the prevention of S. abortus equi infection in different regions and breeds of horses in Xinjiang.